The Antarctic discoveries of the Wilkes Expedition in 1840 : in comparison with the work of other expeditions, especially those of Mawson / copyright . by the American Geographical Society of New York - American Geographical Society of New York (American Geographical Society of New York, 1932)
Relief shown by hachures. Depths shown by soundings in fathoms. Includes index of explorers. "The Geographical Review, Vol. XXII, No. 4, 1932, Pl. V" -- upper right margin. Color 1:3,350,000